Marketing w spółdzielczości rolniczej w Polsce. Podstawy i przesłanki stosowania - Kubiak, Katarzyna (Wydział Prawa i Administracji UAM, 1994)
The article indicates the need to use basic marketing principles in the process of farming cooperatives' adaptation to the current economic conditions. Whereas marketing was formed in connection with the market behaviour of profit-oriented economic entities, a cooperative, apart from being an economic entity, is also an association of persons. Therefore, marketing concepts should be revised in order to be applied to cooperatives. Marketing-mix, consisting of product, price, distribution and promotion policies should have specific features in case of cooperatives. In addition to describing such features, the article presents the premises of the application of marketing techniques in farming cooperatives. Finally, the importance of marketing advising is illustrated with examples drawn from the activities of the Countryside Cooperative Foundation and the Wielkopolska Chamber of Agriculture.
Marketing in Polish farming cooperatives - bases and premises for its use